A review of farm tractor overturning accidents and safety - Abubakar, Mohammed Shu'aibu; Ahmad, Desa; Akande, Fatai Bukola (Universiti Putra Malaysia Press, 2010)
Tractor rollover occurs when a tractor tips sideways or backwards and overturns, potentially crushing the operator. Rollovers are typically considered to occur more frequently during a sharp turn at a high speed on sloping terrains, although data show that rollovers do occur on flat land after hitting obstacles or through inappropriate use and hitching of implements. It is important to highlight that tractor overturns are the major cause of death in farm operations. The overturns are as a result of interactions between the tractor operator, the tractor and the environment. A review of the relevant literature reveals that more than 800 people are killed each year in tractor accidents, and for every person killed, at least 40 others are injured. This paper focuses on tractor overturns because they account for more than half of all the tractor-related deaths. In addition, farm tractor operational safety principles are also highlighted.